Comparison of Post Intubation Complications of Endotracheal Tube and Laryngeal Mask Airway in Pediatrics - Mottaghi, Kamran; Eftekharian, Ali; Salimi, Alireza; Pouyanfar, Anis; Jahangiri, Alireza; Nashibi, Masoud; Mohajerani, Seyed Amir; Malek, Saeed (Annals of Anesthesiology and Critical Care, 2017)
Background: Postoperative sore throat, cough, nausea, apnea, and laryngospasm are common complications of intubation by endotracheal tube (ETT) in pediatrics. The laryngeal mask airway (LMA) is a supraglottic device used as an alternative equipment for ETT in order to decrease the complications. Objectives: To compare the incidence of postoperative sore throat after LMA with ETT in pediatrics. Methods: Seventy-six patients between the ages of 2 - 12 with ASA class I-II who underwent cochlear implant surgery were enrolled and randomly divided into 2 groups including ETT or LMA for airway management. The incidence of complications including sore throat, apnea, vomiting, laryngospasm, post operative cough, intra, and post operative arrhythmia and the influence of these equipment’s on O2 saturation, end tidal CO2, airway pressure, and hemodynamic changes during operation were compared. Wong-Baker facial grimace scale was used to evaluate the severity of pain. Results: The rate of postoperative sore throat and laryngospasm in the ETT group was significantly higher than the LMA group (P = 0.002, 0.011; respectively). Apnea and vomiting were not significantly different. Rate of postoperative cough, incidence of intra, and postoperative arrhythmia were not significantly different between the two groups. Mean arterial pressure, peak airway pressure, end tidal CO2, and oxygen saturation during operation, which was measured continuously, had no significant differences between the two groups. Conclusions: LMA significantly decreases the rate of postoperative sore throat and laryngospasm in pediatrics. However, the rates of apnea, oxygen saturation, and nausea were similar in both groups. Application of LMA as an alternative to ETT is appropriate in pediatric patients.